2015
DOI: 10.1080/00222933.2015.1103910
|View full text |Cite
|
Sign up to set email alerts
|

A gall mite,Aceria rhodiolae(Acari: Eriophyidae), altering the phytochemistry of a medicinal plant,Rhodiola rosea(Crassulaceae), in the Canadian Arctic

Abstract: The eriophyid mite Aceria rhodiolae (G. Canestrini) is known to induce galls on the flowers and leaves of roseroot, Rhodiola rosea L., in subarctic and alpine regions of Europe. After discovering galls on the inflorescences of roseroot in Nunavik (Québec), northeastern Canada, we examined the mites extracted from the galls and compared them with specimens of A. rhodiolae from Europe. Through morphological analyses, we demonstrate that the mites from galls in Nunavik are conspecific with A. rhodiolae from Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, the gall wasp Dryocosmus kuriphilus Yasumatsu could reduce the yield of Castanea sativa Mill. by as much as 80% (Battisti et al, 2014); the gall mite Aceria rhodiolae (Canestrini) could decrease the medicinal quality (salidroside) of Rhodiola rosea L. by over 50% (Beaulieu et al, 2016). Gall-maker larvae acquire nutrition and shelter from plant galls to complete their development (Price, Fernandes & Waring, 1987; Stone & Schönrogge, 2003); therefore, the defoliation and desiccation of plant galls is deadly to these arthropod herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the gall wasp Dryocosmus kuriphilus Yasumatsu could reduce the yield of Castanea sativa Mill. by as much as 80% (Battisti et al, 2014); the gall mite Aceria rhodiolae (Canestrini) could decrease the medicinal quality (salidroside) of Rhodiola rosea L. by over 50% (Beaulieu et al, 2016). Gall-maker larvae acquire nutrition and shelter from plant galls to complete their development (Price, Fernandes & Waring, 1987; Stone & Schönrogge, 2003); therefore, the defoliation and desiccation of plant galls is deadly to these arthropod herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Beaulieu et al (2015) showed phytochemistry alterations in a medicinal plant, roseroot (Rhodiola rosea L.), due to eriophyoid mite infestation, the gall mite Aceria rhodiolae (Canestrini 1892). These authors used salidroside and rosavins as indicators and observed a significant reduction of almost half in salidroside content (45.8%), but not in rosavins.…”
Section: Discussionmentioning
confidence: 99%
“…In many species juvenile instars, dimorph adult forms or males were not described, so they are described afterwards. Additional descriptions and/or redescriptions can be found in following papers: Skoracka et al (2004), Chetverikov (2011), Vidović (2011), Beaulieu et al (2015, Chetverikov et al (2014a), Flechtmann et al (2015, and Xue et al (2015). The impact of slide mounting practice (with or without fibers) on the appearance of the shield pattern was emphasized as an example of possible erroneous conclusions on mite identification (Denizhan et al 2008).…”
Section: Recent Studies (2001-2016)mentioning
confidence: 99%